Investigation of Rare Earth Elements from Coal-Derived Minerals of Sawahlunto Formation and Leaching Behavior Under NaOH and HCl Washing Treatment - Arif Algifari; Fitri Nauli; Andri Van Deni; Siti Aisyah; Dwi Wulan Syakira (Unversitas Muhammadiyah Mataram, 2025)
The growing demand for rare earth elements (REE) in modern technological applications has encouraged the exploration of alternative REE sources, including minerals associated with coal. This study aims to evaluate the potential of minerals in the Sawahlunto Formation coal from the Ombilin Basin as a secondary REE source through an alkaline leaching approach. Coal samples from the Sawahlunto Formation were subjected to alkaline leaching using sodium hydroxide solutions of 200–600 g/L at temperatures of 38–78 °C for 0.5–1.5 hours, followed by an acid-washing stage using 14% hydrochloric acid. X-ray fluorescence analysis identified yttrium, lanthanum, and cesium, with a total initial REE content of approximately 181 ppm. The leaching results show that under optimal conditions 400 g/L NaOH, 78 °C, and a particle size of 60/70 mesh, the residual REE content decreased to 2 ppm, indicating effective dissolution of REE-bearing mineral components. Subsequent acid washing further enhanced REE recovery by removing remaining soluble phases. These results demonstrate that coal from the Sawahlunto Formation possesses promising characteristics as a secondary REE source.